2016
DOI: 10.2147/pgpm.s107772
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 polymorphisms and their influence on risperidone treatment

Abstract: Cytochrome P450 enzyme especially CYP2D6 plays a major role in biotransformation. The interindividual variations of treatment response and toxicity are influenced by the polymorphisms of this enzyme. This review emphasizes the effect of CYP2D6 polymorphisms in risperidone treatment in terms of basic knowledge, pharmacogenetics, effectiveness, adverse events, and clinical practice. Although the previous studies showed different results, the effective responses in risperidone treatment depend on the CYP2D6 polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 100 publications
(120 reference statements)
1
41
0
2
Order By: Relevance
“…The CYP2D6 gene is highly polymorphic, resulting in large individual differences in CYP2D6 enzymatic activity 59 , 60 . Similarly, genetic variants in CYP3A , CYP1A2, and the ABCB1 membrane transporter, P-glycoprotein, have also been suggested to regulate the bioavailability of antipsychotic drugs 61 . Moreover, a recent study highlighted an interaction between pharmacogenetic factors and antipsychotic influences on potassium channel activity as another potential source of individual variation in response 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The CYP2D6 gene is highly polymorphic, resulting in large individual differences in CYP2D6 enzymatic activity 59 , 60 . Similarly, genetic variants in CYP3A , CYP1A2, and the ABCB1 membrane transporter, P-glycoprotein, have also been suggested to regulate the bioavailability of antipsychotic drugs 61 . Moreover, a recent study highlighted an interaction between pharmacogenetic factors and antipsychotic influences on potassium channel activity as another potential source of individual variation in response 62 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CYP2D6 ultra-rapid metabolizers, who have duplicate or multiple functional copies of the CYP2D6 gene, may be at risk for therapeutic failure. There are few studies in adults supporting CYP–risperidone interaction with respect to pharmacokinetics, efficacy, and side effects [ 104 , 105 , 106 , 107 , 108 , 109 ], whereas others have failed to find risperidone–CYP associations [ 110 ]. Some studies have also demonstrated the clinical impact of CYP2D6 genotype in children.…”
Section: Resultsmentioning
confidence: 99%
“…Gaedigk et al[58], and Zineh et al[59], have proposed an Activity Score (AS) that are calculated from the CYP2D6 gene and use to determine the CYP2D6 metabolic activities of an individual. Vanwong et al using risperidone as a probe [60], Puangpetch et al [61], in Thailand, and Dodgen et al in South Africa [31], reported a good correlation between AS, CYP2D6 genotypes and measured phenotypes.…”
Section: Discussionmentioning
confidence: 99%